2019
DOI: 10.1002/glia.23684
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a long noncoding RNA Pcdh17it as a novel marker for immature premyelinating oligodendrocytes

Abstract: Oligodendrocyte precursors (OPs) proliferate and differentiate into oligodendrocytes (OLs) during postnatal development and into adulthood in the central nervous system (CNS). Following the initiation of differentiation, OPs give rise to immature, premyelinating OLs, which undergo further differentiation and mature into myelin‐forming OLs. We identified an immature OL‐specific long noncoding RNA, named Pcdh17it. Through co‐localization analysis and morphological characterization of OLs, we found that Pcdh17it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Recent models using the ablation of Dicer (required for the generation of functional microRNA) or the de novo analysis of oligodendroglial transcriptomic datasets identified microRNAs and lncRNAs that are essential for OPC differentiation. For example, miR-219, miR-338, miR-23, and miR-32, as well as lnc-OL1, lnc-158, and Neat1, promote differentiation, while miR-27a, miR-212, and miR-125-3p inhibit differentiation [109,111,141,[161][162][163][164][165][166][167][171][172][173][174]. Interestingly, these post-transcriptional signals directly regulate some chromatin-modifying genes, suggesting feedback from miRNA and lncRNA regarding chromatin conformation.…”
Section: Post-transcriptional Modifications That Are Essential For Opc Differentiationmentioning
confidence: 99%
“…Recent models using the ablation of Dicer (required for the generation of functional microRNA) or the de novo analysis of oligodendroglial transcriptomic datasets identified microRNAs and lncRNAs that are essential for OPC differentiation. For example, miR-219, miR-338, miR-23, and miR-32, as well as lnc-OL1, lnc-158, and Neat1, promote differentiation, while miR-27a, miR-212, and miR-125-3p inhibit differentiation [109,111,141,[161][162][163][164][165][166][167][171][172][173][174]. Interestingly, these post-transcriptional signals directly regulate some chromatin-modifying genes, suggesting feedback from miRNA and lncRNA regarding chromatin conformation.…”
Section: Post-transcriptional Modifications That Are Essential For Opc Differentiationmentioning
confidence: 99%
“…Subsequent epigenetic profiling for histone marks and genomic occupancy of Sox10, an OL program inducting transcription factor (Stolt et al, ), revealed these lncRNAs are dynamically regulated over the course of OL lineage progression. This led to the functional characterization of lncOL1 (also termed as Pcdh17IT (Kasuga, Fudge, Zhang, & Li, ; Marques et al, ) whose expression was highly correlated with the myeliogenic program. Accordingly, lncOL1 deficient mice had lower OLs around birth and exhibited severe myelination deficits at the peak of myelination.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…Mechanistically, lncOL1 was found to associate with Suz12‐containing PRC2 complex, which deposits H3K27me3, to silence developmental programs that were antagonistic to OL differentiation, thereby allowing differentiation to proceed. Additionally, lncOL1 / Pcdh17IT has been characterized as a specific marker for newly born immature OLs in the developing and adult forebrain of mice (Kasuga et al, ). Since this study, both bulk and single cell transcriptomic studies have expanded the repertoire of lncRNAs expressed in OL lineage cells (Marques et al, ; Marques et al, ; Zeisel et al, ) and have opened the possibility to explore their functional contribution to transitions between different OL subpopulations and glial biology.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…Oligodendrogenesis marker [92] OLMALIN/-AS Regulate oligodendrocyte maturation [93] with mRNA binding protein HuR and activation of Wnt signaling pathway [69]. Furthermore, the enhanced expression of lncRNA brain derived neurotrophic factor antisense (BDNF-AS), which is an antisense RNA that inhibition of BDNF expression in neural growth, was able to inhibit neurite growth in ketamine treated mouse embryonic NSC-derived neurons via activating potassium uptake system protein (TrkB) signaling pathway [70].…”
Section: Pcdh17itmentioning
confidence: 99%
“…Overexpression of lnc158 in NSCs promoted several oligodendrocyte-related genes expressions and strengthened induction of oligodendrocyte lineage differentiation via positively modulation of an organ development regulatory factor-nuclear factor-IB (NFIB) [91]. In addition, an immature OL-specific lncRNA Pcdh17it was proved to be a novel biomarker for newborn immature OLs in the brain development [92]. Interestingly, lncRNA oligodendrocyte maturation-associated long intervening non-coding RNA (OLMALINC) has an identical expression type with its antisense counterpart, OLMALINC-AS, both abundantly expressed in the white matter of human frontal cortex and played vital roles in regulation of human oligodendrocyte maturation related genes [93].…”
Section: The Role Of Lncrnas In Modulation Of Gliogenesismentioning
confidence: 99%